2020
DOI: 10.1183/16000617.0151-2019
|View full text |Cite
|
Sign up to set email alerts
|

Short-course systemic corticosteroids in asthma: striking the balance between efficacy and safety

Abstract: Short courses of systemic corticosteroids (SCS), both oral and injectable, are very effective for the resolution of acute asthma symptoms, including exacerbations. However, the benefits of SCS, even short courses, must be balanced against the impact of their side-effects. While the adverse consequences of long-term use are widely recognised, there appears to be a perception in the medical community that short courses of SCS are safe. Limited but growing evidence in the literature suggests that even very brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 48 publications
1
71
0
2
Order By: Relevance
“…Similarly, treatment of exacerbations using OCS bursts was assumed not to result in any increase in OCS-related adverse events even though we acknowledge that there is increasing evidence that cumulative doses of short-term OCS bursts contribute to corticosteroid morbidity as well. (48,49) In addition, as longer-term RCT data was not available, the reduction in mOCS dose with long-term use of mepolizumab was capped at 30%, in line with results from the 24-week SIRIUS study. Nevertheless, data inputs relating to adverse events from mOCS were not found to be drivers of our model and are likely to have little impact on the ICER.…”
Section: Accepted Manuscriptmentioning
confidence: 53%
“…Similarly, treatment of exacerbations using OCS bursts was assumed not to result in any increase in OCS-related adverse events even though we acknowledge that there is increasing evidence that cumulative doses of short-term OCS bursts contribute to corticosteroid morbidity as well. (48,49) In addition, as longer-term RCT data was not available, the reduction in mOCS dose with long-term use of mepolizumab was capped at 30%, in line with results from the 24-week SIRIUS study. Nevertheless, data inputs relating to adverse events from mOCS were not found to be drivers of our model and are likely to have little impact on the ICER.…”
Section: Accepted Manuscriptmentioning
confidence: 53%
“…The study by van Boven et al [14] also showed that almost 50% of non-adherent patients used two or more courses of oral corticosteroids and antibiotics over the course of the year. The prescription of frequent courses of steroids is common, as there appears to be a perception in the medical community that the benefit of a short burst of steroids is much higher than the risk, especially when used judiciously [28]. That said, taking more than four standard short courses of oral corticosteroid significantly increases the lifetime risk of pneumonia and Cushing syndrome-type sideeffects, including type 2 diabetes, cardiovascular diseases, osteoporosis and cataracts [29].…”
Section: Excessive Oral Corticosteroid and β-Agonist Usementioning
confidence: 99%
“…Chronic rhinosinusitis with nasal polyps (CRSwNP) is a prevalent condition characterised by a significant impact on quality of life and productivity, with frequent recurrence after both medical and surgical treatments 1 . Oral corticosteroids are effective at achieving short‐term symptom improvement, 2,3 but benefit is limited due to the risk of side effects which accrue with repeated use 4 . Surgery has been shown to achieve more durable symptomatic benefits, 5 but is associated with pain and discomfort, time for recovery, a small but definite risk of serious complications, 6 and, based on previous data, more than 1 in 5 patients will require another surgery within 5 years of follow‐up 5 .…”
Section: Introductionmentioning
confidence: 99%